Term length and public finances: The case of U.S. governors - Jonas Klarin (Uppsala University, Department of Economics, 2019)
This paper studies how a politician's term length affects public finances. I test whether the gradual increase from two- to four-year terms for American governors affects state finances using a rich state-year panel stretching back almost a century. The results show that adopting four-year terms decreases annual expenditures and revenues by 6 %. The effect of the reform is present immediately after voters approve the ballot measure, when the last two-year-term governor is still in office, which suggests that the mechanism at work is stronger re-election incentives for the incumbent. The effect is larger among electorally "at risk" governors. Democratic governors respond to longer terms by increasing public employment instead of decreasing expenditures.
urn:nbn:se:uu:diva-383043
Keywords: 330; Term Length; U.S. Governors; Political Agency; Elections